Kragelundovnen - Jessen, Anne Birgitte (Hikuin, 2001)
The Kragelund kiln By Anne Birgitte Jessen In 1984 a kiln was excavated in the village of Kragelund near Silkeborg. The kiln contained a flue and a kiln chamber placed horizontally in relation to each other, which classes it as a double-chambered horizontal kiln. The floor of the kiln was covered with clay. The kiln chamber contained a tongue-shaped platform, which was probably totally covered with clay. On each side of the platform was a rising flue. It is unknown whether the flue was as long as the kiln chamber or whether the flue rose to the level of the platform. The kiln was covered with a clay dome built up without any kind of osiers. It is likely that the back of the kiln had a loading aperture because it would have eased access to the kiln chamber, but the kiln was too badly preserved to determine whether an opening existed. Neither repairs nor rebuilding was observed during the excavation. There was no sign of other kilns in the area. The presence of only one kiln with one kiln phase this indicates that the pottery in Kragelund only existed for a short period of time. The ceramics found together with the kiln points towards a dating in the 14th century. This dating is supported by C-14 analysis.